Composite forward osmosis membrane as well as preparation method and reverse salt diffusion lithium extraction application thereof
By modifying the hydrophobic membrane and forming a composite cortex, the problem of reverse salt diffusion in forward permeation is solved, efficient separation and stability of magnesium lithium is achieved, and innovation and application of lithium extraction technology in salt lakes is promoted.
Patent Information
- Application Number
- CN202411873312.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-29
AI Technical Summary
During the forward penetration process, reverse salt diffusion leads to liquid contamination, and it is difficult for the prior art to effectively separate magnesium lithium, especially in the salt lake lithium extraction.
The hydrophobic membrane is hydrophilicly modified by a modified monomer aqueous solution and an oxidant, and self-assemble and interfacial polymerize on the surface of the modified membrane to form a composite cortex to improve the separation performance of magnesium lithium.
It achieves efficient separation of magnesium lithium, reduces reverse salt diffusion, improves the long-term operation stability and economic feasibility of the membrane, and has broad industrial application potential.
Smart Images

Figure CN119896978A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of osmotic membranes, and in particular to a composite forward osmosis membrane, a preparation method thereof, and an application of reverse salt diffusion in lithium extraction. Background Art
[0002] Forward osmosis is a membrane separation technology that relies on the osmotic pressure difference formed by the solution concentration difference on both sides of the membrane as a driving force to drive the spontaneous transfer and separation of molecules on both sides. Forward osmosis does not require additional pressure and has the characteristics of low energy consumption and environmental sustainability. Therefore, forward osmosis membrane separation technology has application potential in the fields of juice concentration, water bags, sludge concentration, etc. A typical forward osmosis membrane is mainly composed of a lower porous substrate (support layer) and an upper dense polyamide selective layer (cortex), which is an asymmetric membrane structure. The support layer mainly plays a role in maintaining the stability of the membrane structure, while the cortex is crucial for the retention and concentration of the driving liquid substance.
[0003] However, in the forward osmosis process, reverse salt diffusion is an inevitable defect, that is, the solute in the driving solution diffuses through the forward osmosis membrane to the feed solution, causing the feed solution to be contaminated. During the forward osmosis operation, the monovalent salt in the driving solution is usually difficult to intercept, resulting in divalent salts being widely used as driving solutions. However, this defect has great potential application prospects in the separation of divalent and monovalent ions, especially in the extraction of lithium from salt lakes. Lithium, as a strategic metal, is mainly stored in salt lakes. The key to extracting lithium from salt lakes is lithium (monovalent Li + ) / Magnesium (divalent Mg 2+ ) separation. This is because the salt lake brine contains a large amount of Mg 2+ Mg 2+ and Li + The hydration radius of Mg is similar to that of Li, so it is difficult to extract lithium from brine by traditional methods. Currently, there is no research on the separation of Mg by reverse salt osmosis using forward osmosis membranes. 2+ / Li + Therefore, under pressureless conditions, Mg is achieved through forward osmosis membrane 2+ / Li + Separation, creating an innovative, energy-saving and environmentally friendly lithium extraction technology, is of great significance.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a composite forward osmosis membrane and a preparation method thereof and reverse salt diffusion lithium extraction application, aiming to use the forward osmosis membrane to achieve Mg 2+ / Li +Separation, and simplify the preparation process of forward osmosis membranes, promoting the wider application of forward osmosis membranes.
[0006] The technical solution of the present invention is as follows:
[0007] A first aspect of the present invention provides a method for preparing a composite forward osmosis membrane, comprising the steps of:
[0008] S1, wetting the hydrophobic membrane with an organic solvent, then immersing it in a modified monomer aqueous solution, adding an oxidant to the modified monomer aqueous solution, stirring and standing in sequence to obtain a modified membrane, taking out the modified membrane and then rinsing it with water;
[0009] S2, first pouring a polyanion solution onto the surface of one side of the modified membrane and reacting it for a first predetermined time, and removing excess polyanion solution; then pouring a polyethyleneimine aqueous solution into it and reacting it for a second predetermined time, and removing excess polyethyleneimine aqueous solution; then pouring an organic solution containing trimesoyl chloride into it and reacting it for a third predetermined time, and removing excess organic solution containing trimesoyl chloride, thereby forming a composite cortex on the surface of one side of the modified membrane; and finally, standing and heat treating it to obtain the composite forward osmosis membrane.
[0010] Optionally, the hydrophobic membrane is one of a polyethylene microporous membrane, a polypropylene membrane, a polyvinylidene fluoride membrane and a polytetrafluoroethylene membrane, and the thickness of the hydrophobic membrane is 5 μm to 20 μm.
[0011] Optionally, the modified monomer aqueous solution is one or more of an aqueous solution of m-phenylenediamine, an aqueous solution of aniline, an aqueous solution of o-phenylenediamine and an aqueous solution of p-phenylenediamine.
[0012] Optionally, the concentration of the modified monomer aqueous solution is 0.2 wt% to 0.6 wt%.
[0013] Optionally, the oxidant is potassium persulfate, sodium persulfate, hydrogen peroxide, silver nitrate, Fe 3+ , Cu 2+ 、Ni 2+ One or more of .
[0014] Optionally, based on the system consisting of the modified monomer aqueous solution and the oxidant, the concentration of the oxidant is 40 g / L to 80 g / L.
[0015] Optionally, the polyanion solution is one or more of a sodium alginate solution, a polyacrylic acid solution, a sodium polystyrene sulfonate solution, a graphene oxide solution, a polyethylene sulfonic acid solution, and a sodium carboxymethyl cellulose solution.
[0016] Optionally, the concentration of the polyanion solution is 2 g / L to 8 g / L.
[0017] Optionally, the concentration of the polyethyleneimine aqueous solution is 2 wt% to 7 wt%.
[0018] Optionally, in step S2, the first predetermined time is 5 minutes to 10 minutes, the second predetermined time is 5 minutes to 10 minutes, and the third predetermined time is 1 minute to 2 minutes.
[0019] Optionally, in step S1, the stirring time is 1 min to 10 min, and the standing time is 2 h to 5 h.
[0020] Optionally, in step S2, the standing still specifically includes the step of: standing still in the air for 1 min to 5 min; the heat treatment specifically includes the step of: heat treatment at 40° C. to 60° C. for 5 min to 10 min.
[0021] The second aspect of the present invention provides a composite forward osmosis membrane prepared by the preparation method of the present invention.
[0022] The third aspect of the present invention provides an application of reverse salt diffusion lithium extraction of the composite forward osmosis membrane described in the present invention, wherein the reverse salt diffusion lithium extraction application is to separate magnesium and lithium in a magnesium-lithium mixed solution, to extract lithium in salt lake brine, or to extract lithium in a leachate of waste lithium batteries.
[0023] Beneficial effects: The present invention provides a method for preparing a composite forward osmosis membrane, wherein the hydrophobic membrane is firstly hydrophilically modified by using a modified monomer aqueous solution and an oxidant, and then a reaction of layer-by-layer self-assembly at the bottom and interfacial polymerization at the top is carried out on the surface of the modified membrane, wherein polyethyleneimine can act as a polycation and a polyanion for layer-by-layer self-assembly, and can also act as an aqueous phase for interfacial polymerization with trimesoyl chloride, thereby forming a composite cortex on the surface of the modified membrane. The method is simple to operate, the steps are simplified, and the cost is reduced. The prepared composite forward osmosis membrane has excellent magnesium-lithium separation performance and long-term operation stability, and shows great potential in terms of economic feasibility, efficiency, selectivity and future industrial applications, especially in magnesium-lithium separation, lithium extraction in salt lake brine and lithium extraction in waste lithium battery leachate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The present invention provides a flow chart for preparing a composite forward osmosis membrane.
[0025] Figure 2 This is a physical picture of the original PE film and the modified PE film in Example 1.
[0026] Figure 3 These are SEM images of the original PE film and the modified PE film in Example 1.
[0027] Figure 41 is a SEM image of the forward osmosis membranes prepared in Example 1, Example 2, Example 3 and Comparative Example 1.
[0028] Figure 5 The data comparison diagram is of water flux and reverse salt flux of the forward osmosis membranes prepared in Examples 1 to 3 and Comparative Example 1 in AL-DS mode and AL-FS mode when 1M NaCl solution is used as the draw solution.
[0029] Figure 6 The data comparison chart is a graph showing the water flux, magnesium-lithium ratio in the feed solution and magnesium-lithium retention rate of the forward osmosis membranes prepared in Examples 1 to 3 and Comparative Example 1 in the AL-DS mode and the AL-FS mode when the magnesium-lithium mixed solution is used as the draw solution.
[0030] Figure 7 The graph is a comparison of the membrane permeation rates of the composite forward osmosis membranes prepared in Examples 1 to 3 in the AL-DS mode and the AL-FS mode when the magnesium-lithium mixed solution is used as the draw solution.
[0031] Figure 8 This is a data comparison chart of the water flux and the magnesium-lithium ratio in the feed solution of the composite forward osmosis membrane prepared in Example 1 when mixed solutions with different magnesium-lithium ratios are used as the draw solution.
[0032] Fig. 9 This is a magnesium-lithium separation performance diagram of the composite forward osmosis membrane prepared in Example 1 when it is operated for a long time with a magnesium-lithium mixed solution as the drawing liquid. DETAILED DESCRIPTION
[0033] The present invention provides a composite forward osmosis membrane and a preparation method thereof and reverse salt diffusion lithium extraction application. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a composite forward osmosis membrane, which comprises the steps of:
[0035] S1, wetting the hydrophobic membrane with an organic solvent, then immersing it in a modified monomer aqueous solution, adding an oxidant to the modified monomer aqueous solution, stirring and standing in sequence to obtain a modified membrane, taking out the modified membrane and then rinsing it with water;
[0036] S2, first pouring a polyanion solution onto the surface of one side of the modified membrane and reacting it for a first predetermined time, and removing excess polyanion solution; then pouring a polyethyleneimine aqueous solution into it and reacting it for a second predetermined time, and removing excess polyethyleneimine aqueous solution; then pouring an organic solution containing trimesoyl chloride into it and reacting it for a third predetermined time, and removing excess organic solution containing trimesoyl chloride, thereby forming a composite cortex on the surface of one side of the modified membrane; and finally, standing and heat treating it to obtain the composite forward osmosis membrane.
[0037] In this embodiment, the hydrophobic membrane is first hydrophilically modified by a modified monomer aqueous solution and an oxidant, and then a reaction of layer-by-layer self-assembly (LBL) at the bottom and interfacial polymerization (IP) at the top is carried out on the surface of the modified membrane, wherein polyethyleneimine can act as a polycation and a polyanion for layer-by-layer self-assembly, and can also act as an aqueous phase for interfacial polymerization with trimesoyl chloride (oil phase), thereby forming a composite loose cortex (active layer) on the surface of the modified membrane. The method is simple to operate, the steps are simplified, and the cost is reduced. The prepared composite forward osmosis membrane has excellent magnesium-lithium separation performance and long-term operation stability, and shows great potential in terms of economic feasibility, efficiency, selectivity and future industrial applications, especially in magnesium-lithium separation, lithium extraction in salt lake brine and lithium extraction in waste lithium battery leachate. It has great application potential.
[0038] In this embodiment, in step S1, the hydrophobic membrane is first moistened with an organic solvent so that the modified monomer aqueous solution can fully enter the membrane pores, and then the hydrophobic membrane is immersed in the modified monomer aqueous solution so that both sides of the membrane are directly in contact with the solution, so that the modification effects on both sides of the membrane are close and the inside of the membrane is better modified. An oxidant is added to the modified monomer aqueous solution to accelerate the oxidative polymerization process of the modified monomer, the solution is gently stirred to make the solution uniform, and then it is allowed to stand at room temperature for a period of time to allow the modified monomer to undergo in-situ chemical oxidative polymerization on the membrane surface to form a polymerized modified coating, thereby achieving hydrophilic modification of the hydrophobic membrane.
[0039] In this embodiment, in step S2, a polyanion solution, a polyethyleneimine aqueous solution and an organic solution containing trimesoyl chloride are sequentially poured onto the surface of the modified membrane, and the reaction is performed for the predetermined time, respectively, to perform layer-by-layer self-assembly at the bottom and interfacial polymerization at the top, wherein the polyethyleneimine can act as a polycation and the first added polyanion to perform layer-by-layer self-assembly and cross-deposit on the surface of the modified membrane through electrostatic action, and can also act as an aqueous phase and perform interfacial polymerization with the later added trimesoyl chloride (as an oil phase), thereby forming a composite cortex on the surface of the modified membrane. Finally, the composite forward osmosis membrane is obtained by standing and heat treatment.
[0040] In some embodiments, the hydrophobic membrane (as substrate) may be, but is not limited to, a polyethylene microporous membrane, and may also be selected from other hydrophobic membranes, such as a polypropylene membrane, a polyvinylidene fluoride membrane, and a polytetrafluoroethylene membrane. Preferably, the hydrophobic membrane is a polyethylene microporous membrane.
[0041] In some embodiments, the hydrophobic film has a thickness of 5 μm to 20 μm, for example, 5 μm, 10 μm, 15 μm or 20 μm.
[0042] In some embodiments, the organic solvent used to wet the hydrophobic membrane may be one or more of ethanol, methanol, isopropanol, and acetone. Preferably, the organic solvent used to wet the hydrophobic membrane is ethanol.
[0043] In some embodiments, the modified monomer aqueous solution is one or more of an aqueous solution of m-phenylenediamine, an aqueous solution of aniline, an aqueous solution of o-phenylenediamine, and an aqueous solution of p-phenylenediamine.
[0044] In some embodiments, the concentration of the modified monomer aqueous solution is 0.2 wt% to 0.6 wt%, such as 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%. Preferably, the concentration of the modified monomer aqueous solution is 0.3 wt%.
[0045] In some embodiments, the oxidant is a persulfate (e.g., potassium persulfate, sodium persulfate), hydrogen peroxide, silver nitrate, Fe 3+ , Cu 2+ 、Ni 2+ Preferably, the oxidant is potassium persulfate.
[0046] In some embodiments, based on the system consisting of the modified monomer aqueous solution and the oxidant, the concentration of the oxidant is 40 g / L to 80 g / L, for example, 40 g / L, 50 g / L, 60 g / L, 70 g / L, 80 g / L. Preferably, the concentration of the oxidant is 50 g / L.
[0047] In some embodiments, in step S1, the stirring time is 1 min to 10 min (for example, 5 min), and the standing time is 2 h to 5 h (for example, 3 h).
[0048] In some embodiments, the polyanion solution is one or more of a sodium alginate solution, a polyacrylic acid solution, a sodium polystyrene sulfonate solution, a graphene oxide solution, a polyvinyl sulfonic acid solution, and a sodium carboxymethyl cellulose solution. Preferably, the polyanion solution is a sodium alginate solution.
[0049] In some embodiments, the concentration of the polyanion solution is 2 g / L to 8 g / L, for example, 2 g / L, 3 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L. Preferably, the concentration of the polyanion solution is 6 g / L.
[0050] In some embodiments, the concentration of the polyethyleneimine aqueous solution is 2wt% to 7wt%, for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%. Preferably, the concentration of the polyethyleneimine aqueous solution is 4wt%. The forward osmosis membrane prepared by the polyethyleneimine aqueous solution within the concentration range has good magnesium-lithium separation performance, and the forward osmosis membrane prepared when the concentration is 4wt% has the best magnesium-lithium separation performance.
[0051] In some embodiments, the organic solution (oil phase) containing trimesoyl chloride is prepared by dissolving trimesoyl chloride in an organic solvent. The organic solvent may be, but is not limited to, n-hexane, or an Isopar series, toluene, xylene, ethyl acetate, or a mixture thereof.
[0052] In some embodiments, the first predetermined time is 5 min to 10 min (for example, 5 min), the second predetermined time is 5 min to 10 min (for example, 5 min), and the third predetermined time is 1 min to 2 min (for example, 1 min).
[0053] In some embodiments, in step S2, the standing specifically includes the step of standing in air for 1 min to 5 min (e.g., 1 min, 2 min, 3 min, 4 min, 5 min); the heat treatment specifically includes the step of heat treatment at 40°C to 60°C (e.g., 40°C, 50°C, 60°C) for 5 min to 10 min (e.g., 5 min, 6 min, 7 min, 8 min, 9 min, 10 min). The purpose of the standing is to promote the interfacial polymerization reaction, and the purpose of the heat treatment is to promote the interfacial polymerization reaction and improve the separation performance and stability of the membrane.
[0054] In some embodiments, the method for preparing the composite forward osmosis membrane specifically comprises the steps of:
[0055] S11, wetting the polyethylene microporous membrane with ethanol, then immersing it in an aqueous solution of m-phenylenediamine, adding potassium persulfate to the aqueous solution of m-phenylenediamine, stirring for 1 min to 10 min and standing for 2 h to 5 h in sequence to obtain a modified membrane, taking out the modified membrane and rinsing it with water;
[0056] S12, first pouring sodium alginate solution into the surface of one side of the modified membrane and reacting it for 5min to 10min, removing the excess sodium alginate solution and washing with water; then pouring polyethyleneimine aqueous solution into it and reacting it for 5min to 10min, removing the excess polyethyleneimine aqueous solution and blowing the membrane surface dry with nitrogen; then pouring an organic solution containing trimesoyl chloride into it and reacting it for 1min to 2min, removing the excess organic solution containing trimesoyl chloride; finally, standing it in the air for 1min to 5min and heat-treating it at 40℃ to 60℃ for 5min to 10min to obtain the composite forward osmosis membrane.
[0057] An embodiment of the present invention provides a composite forward osmosis membrane, wherein the composite forward osmosis membrane is prepared by the preparation method described in any of the aforementioned embodiments.
[0058] An embodiment of the present invention provides an application of reverse salt diffusion lithium extraction of the composite forward osmosis membrane described in the aforementioned embodiment, wherein the reverse salt diffusion lithium extraction application is to separate magnesium and lithium in a magnesium-lithium mixed solution, to extract lithium in salt lake brine, or to extract lithium in a leachate of waste lithium batteries.
[0059] The present invention will be further described below by means of specific examples.
[0060] Example 1
[0061] This embodiment provides a method for preparing a composite forward osmosis membrane, which is as follows:
[0062] Preparation of modified membrane: Wet a polyethylene microporous membrane (PE membrane, thickness 9 μm) with ethanol, and then immerse it in a 0.3wt% m-phenylenediamine (MPD) aqueous solution so that both sides of the membrane are in direct contact with the solution. Then add 50g / L potassium persulfate (50mL) to the MPD aqueous solution, gently stir the solution for 5min, and then let it stand at room temperature for 3h to allow MPD to undergo in-situ chemical oxidation polymerization on the surface of the PE membrane fiber to form a PMPD coating, thereby achieving hydrophilic modification of the PE membrane. Take out the modified membrane and rinse it thoroughly with deionized water to obtain a modified PE membrane (PMPE).
[0063] The composite skin layer was prepared on the surface of the modified membrane by layer-by-layer self-assembly (LBL) and interfacial polymerization (IP): First, a certain amount of 6g / L sodium alginate (SA) solution was poured on one side of the modified PE membrane and reacted for 5min. Then the SA solution was poured out and the membrane was washed three times with deionized water. Subsequently, a certain amount of 4wt% polyethyleneimine (PEI) aqueous solution was poured on the same side of the membrane, and the PEI aqueous solution was poured out after 5min and the residual water phase on the membrane surface was blown dry with nitrogen, which made the polyanion SA and polycation PEI cross-deposited on the surface of the modified PE membrane through electrostatic action to form an LBL layer. Then a certain amount of n-hexane solution (oil phase) containing trimesoyl chloride (TMC) was poured on the same side of the membrane to undergo interfacial polymerization with PEI, and the oil phase was poured out after 1min, and the membrane was left to stand in the air for 2min, and finally the membrane was heat-treated in a 60℃ oven for 8min to obtain a composite forward osmosis membrane, which was taken out and stored in deionized water.
[0064] Example 2
[0065] The preparation method of Example 2 is the same as that of Example 1, except that the 4 wt % aqueous polyethyleneimine solution in Example 1 is replaced by a 2 wt % aqueous polyethyleneimine solution.
[0066] Example 3
[0067] The preparation method of Example 2 is the same as that of Example 1, except that the 4 wt % aqueous polyethyleneimine solution in Example 1 is replaced by a 7 wt % aqueous polyethyleneimine solution.
[0068] Comparative Example 1
[0069] The preparation method of Comparative Example 1 is different from the preparation method of Example 1 in that the sodium alginate solution is not coated on the surface of the modified PE film, and only interfacial polymerization is performed, as follows:
[0070] Preparation of modified membrane: Wet the PE membrane (9 μm thick) with ethanol and then immerse it in a 0.3 wt% MPD aqueous solution so that both sides of the membrane are in direct contact with the solution. Then add 50 g / L potassium persulfate (50 mL) to the MPD aqueous solution, gently stir the solution for a few minutes, and then let it stand at room temperature for 3 hours to allow the MPD to undergo in-situ chemical oxidation polymerization on the surface of the PE membrane fiber to form a PMPD coating, thereby achieving hydrophilic modification of the PE membrane. Take out the modified membrane and rinse it thoroughly with deionized water to obtain a modified PE membrane.
[0071] The cortex was prepared on the surface of the modified membrane by interfacial polymerization: first, a certain amount of 4wt% PEI aqueous solution was poured on one side of the modified PE membrane. After 5 minutes, the PEI aqueous solution was poured out and the residual water phase on the membrane surface was blown dry with nitrogen. Then, a certain amount of n-hexane solution (oil phase) containing trimesoyl chloride (TMC) was poured on the same side of the membrane to undergo interfacial polymerization with PEI. After 1 minute, the oil phase was poured out and the membrane was allowed to stand in the air for 2 minutes. Finally, the membrane was heat-treated in an oven at 60°C for 8 minutes to obtain a forward osmosis membrane. The membrane was taken out and stored in deionized water.
[0072] The forward osmosis membranes prepared in Examples 1 to 3 and Comparative Example 1 were characterized and their performances were tested.
[0073] Figure 2 These are the physical pictures of the original PE film and the modified PE film in Example 1, wherein Figure a is a physical picture of the original PE film, and Figure b is a physical picture of the modified PE film.
[0074] Figure 3 The scanning electron microscope (SEM) images of the original PE membrane and the modified PE membrane in Example 1, wherein Figure a is the SEM image of the original PE membrane, and Figure b is the SEM image of the modified PE membrane (PMPE). According to the figure, the original PE membrane presents a porous structure composed of interconnected PE fibers. After modification, the PE fibers are wrapped by PMPD, and the pore size of the PE membrane surface is slightly reduced, but it still presents a porous structure.
[0075] Figure 4 It is the SEM picture of the forward osmosis membrane obtained in Example 1, Example 2, Example 3 and Comparative Example 1, wherein Figure a is the SEM picture of the forward osmosis membrane obtained in Example 1, Figure b is the SEM picture of the forward osmosis membrane obtained in Example 2, Figure c is the SEM picture of the forward osmosis membrane obtained in Example 3, and Figure d is the SEM picture of the forward osmosis membrane obtained in Comparative Example 1. According to the figure, there are almost no obvious holes on the surface of the forward osmosis membrane obtained in Example 1, Example 2 and Example 3, and an obvious Turing structure is presented, while there are some holes on the surface of the forward osmosis membrane obtained in Comparative Example 1.
[0076] The forward osmosis performance of the forward osmosis membranes prepared in Examples 1 to 3 and Comparative Example 1 was tested. The specific test method was as follows: a laboratory-scale forward osmosis cross-flow device was used for testing, the membrane surface flow rate was 1.3 cm / s, deionized water was used as the feed liquid, and 1M NaCl solution was used as the draw liquid. The two operating modes were operated for 2 hours, and the water flux and reverse salt flux were measured, namely, the pressure delayed osmosis mode (AL-DS mode), in which the draw liquid flows along the membrane active layer, and the FO mode (AL-FS mode), in which the feed liquid flows along the membrane active layer.
[0077] The water flux (J) was calculated by the following formula: w ):
[0078]
[0079] Among them, ΔV(L) is the water permeation during the test time, A is the effective surface area of the membrane, and Δt(h) is the actual test time.
[0080] The reverse salt flux (J) was calculated by the following formula: S , gm -2 h -1 , abbreviated as gMH):
[0081]
[0082] Among them, C t (g / L) and V t (L) are the solution concentration and solution volume of the raw material solution at time t, C0 (g / L) and V0 (L) are the original solution concentration and solution volume of the raw material solution, A is the effective surface area of the membrane, and Δt (h) is the actual test time.
[0083] Figure 5 The data comparison diagram of the water flux and reverse salt flux of the forward osmosis membranes prepared in Examples 1 to 3 and Comparative Example 1 in AL-DS mode and AL-FS mode when 1M NaCl solution is used as the draw liquid, wherein Figure a is in AL-DS mode and Figure b is in AL-FS mode. According to the figure, it can be seen that in both operation modes, the water flux of Examples 1 to 3 is significantly improved compared with Comparative Example 1, and the reverse salt flux is also significantly reduced, among which the water flux of Example 1 is the highest, the reverse salt flux is the lowest, and the forward osmosis performance of the composite forward osmosis membrane is the best.
[0084] The forward osmosis membranes prepared in Examples 1 to 3 and Comparative Example 1 were tested for magnesium-lithium separation performance. The specific test method was as follows: a laboratory-scale forward osmosis cross-flow device was used for testing, the membrane surface flow rate was 1.3 cm / s, deionized water was used as the feed liquid, and the magnesium-lithium mixed solution (Mg 2+ The concentration is 10g / L, Li + The draw solution was a Mg / Li ratio of 20 (with a concentration of 0.5 g / L) and the water flux, the Mg / Li ratio in the feed solution and the Mg / Li retention rate were measured under two operation modes, namely, the pressure retarded osmosis mode (AL-DS mode), in which the draw solution flowed along the membrane active layer, and the FO mode (AL-FS mode), in which the feed solution flowed along the membrane active layer.
[0085] Figure 6The data comparison diagram of the water flux, magnesium-lithium ratio in the feed solution and magnesium-lithium retention rate of the forward osmosis membrane prepared in Examples 1 to 3 and Comparative Example 1 when the magnesium-lithium mixed solution is used as the draw solution in the AL-DS mode and the AL-FS mode, wherein Figure a is in the AL-DS mode and Figure b is in the AL-FS mode. It can be seen from the figure that in the two operation modes, compared with Comparative Example 1, the water flux of Examples 1 to 3 is significantly improved, the magnesium-lithium ratio in the feed solution is significantly reduced, and the Mg 2+ The interception rate of Example 1 is significantly improved, among which the water flux of Example 1 is the highest, the magnesium-lithium ratio in the feed solution is the lowest, and the magnesium-lithium separation performance of the membrane is the best. At the same time, we can see that when Example 1 is running in AL-FS mode, Mg 2+ The interception rate is the highest, Li + The interception rate is the lowest, the magnesium-lithium ratio in the feed liquid is the lowest, and it has the best magnesium-lithium separation performance.
[0086] Figure 7 The comparison diagram of the membrane permeation rate of the composite forward osmosis membrane prepared in Examples 1 to 3 in the AL-DS mode and the AL-FS mode when the magnesium-lithium mixed solution is used as the draw solution. It can be seen from the figure that Li + The penetration rate is much higher than that of Mg 2+ This indicates that the composite forward osmosis membranes prepared in Examples 1 to 3 all have the performance of magnesium-lithium separation, among which the Mg 2+ The penetration rate was the lowest, which indicates that its 2+ It has a good interception effect.
[0087] The composite forward osmosis membrane prepared in Example 1 was tested for magnesium-lithium separation performance when mixed solutions with different magnesium-lithium ratios were used as the draw solution. The specific test method was as follows: a laboratory-scale forward osmosis cross-flow device was used for testing, the membrane surface flow rate was 1.3 cm / s, deionized water was used as the feed solution, and mixed solutions with different magnesium-lithium ratios (Mg 2+ and Li + The total mixed concentration was 10 g / L, and the magnesium-lithium ratios were 20, 40, 60 and 80, respectively, as the draw solution. The water flux and the magnesium-lithium ratio in the feed solution were measured under FO mode (AL-FS mode, that is, the feed solution flows along the membrane active layer).
[0088] Figure 8 This is a data comparison chart of the water flux and the magnesium-lithium ratio in the feed solution of the composite forward osmosis membrane prepared in Example 1 when mixed solutions with different magnesium-lithium ratios are used as the draw liquid. According to the figure, it can be seen that as the mixed solution with gradually increasing magnesium-lithium ratio is used as the draw liquid, the water flux will gradually increase, the magnesium-lithium ratio in the feed solution will be greatly reduced, and both have good magnesium-lithium separation performance.
[0089] The composite forward osmosis membrane prepared in Example 1 was tested for magnesium-lithium separation performance after long-term operation. The specific test method was as follows: a laboratory-scale forward osmosis cross-flow device was used for testing, the membrane surface flow rate was 1.3 cm / s, deionized water was used as the feed liquid, and the magnesium-lithium mixed solution (Mg 2+ The concentration is 10g / L, Li + The concentration of 0.5 g / L and the magnesium-to-lithium ratio of 20) were used as the draw solution. The system was operated continuously for 30 h in FO mode (AL-FS mode, i.e., the feed solution flows along the membrane active layer). The water flux, magnesium-to-lithium ratio in the feed solution, and Li + concentration.
[0090] Fig. 9 The magnesium-lithium separation performance diagram of the composite forward osmosis membrane prepared in Example 1 when using a magnesium-lithium mixed solution as the draw solution for a long time, wherein Figure a shows the data of water flux and magnesium-lithium ratio in the feed solution, and Figure b shows the data of Li in the feed solution + According to the figure, it can be seen that even if the composite forward osmosis membrane prepared in Example 1 is continuously operated for 30 hours, the magnesium-lithium ratio in the feed solution is stably maintained below 3.5, and Li + The concentration can reach 280.4 mg / L, with good long-term stable magnesium-lithium separation performance.
[0091] In summary, the present invention provides a composite forward osmosis membrane and a preparation method and application thereof. The method is simple to operate, has simplified steps, and reduces costs. The prepared composite forward osmosis membrane has excellent magnesium-lithium separation performance and long-term operation stability, and shows great potential in economic feasibility, efficiency, selectivity, and future industrial applications, especially in magnesium-lithium separation, lithium extraction in salt lake brine, and lithium extraction in waste lithium battery leachate. It has great application potential.
[0092] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a composite forward osmosis membrane, characterized in that: Includes steps: S1, wetting the hydrophobic membrane with an organic solvent, then immersing it in a modified monomer aqueous solution, adding an oxidant to the modified monomer aqueous solution, stirring and standing in sequence to obtain a modified membrane, taking out the modified membrane and then rinsing it with water; S2, first pouring a polyanion solution onto the surface of one side of the modified membrane and reacting it for a first predetermined time, and removing excess polyanion solution; then pouring a polyethyleneimine aqueous solution into it and reacting it for a second predetermined time, and removing excess polyethyleneimine aqueous solution; then pouring an organic solution containing trimesoyl chloride into it and reacting it for a third predetermined time, and removing excess organic solution containing trimesoyl chloride, thereby forming a composite cortex on the surface of one side of the modified membrane; and finally, standing and heat treating it to obtain the composite forward osmosis membrane.
2. The method for preparing a composite forward osmosis membrane according to claim 1, wherein The hydrophobic membrane is one of a polyethylene microporous membrane, a polypropylene membrane, a polyvinylidene fluoride membrane and a polytetrafluoroethylene membrane, and the thickness of the hydrophobic membrane is 5 μm to 20 μm.
3. The method for preparing a composite forward osmosis membrane according to claim 1, wherein The modified monomer aqueous solution is one or more of an aqueous solution of m-phenylenediamine, an aqueous solution of aniline, an aqueous solution of o-phenylenediamine and an aqueous solution of p-phenylenediamine; The concentration of the modified monomer aqueous solution is 0.2 wt% to 0.6 wt%.
4. The method for preparing a composite forward osmosis membrane according to claim 1, wherein The oxidant is potassium persulfate, sodium persulfate, hydrogen peroxide, silver nitrate, Fe 3+ , Cu 2+ 、Ni 2+ One or more of; Based on the system consisting of the modified monomer aqueous solution and the oxidant, the concentration of the oxidant is 40 g / L to 80 g / L.
5. The method for preparing a composite forward osmosis membrane according to claim 1, wherein The polyanion solution is one or more of a sodium alginate solution, a polyacrylic acid solution, a sodium polystyrene sulfonate solution, a graphene oxide solution, a polyethylene sulfonic acid solution, and a sodium carboxymethyl cellulose solution; The concentration of the polyanion solution is 2 g / L to 8 g / L.
6. The method for preparing a composite forward osmosis membrane according to claim 1, wherein The concentration of the polyethyleneimine aqueous solution is 2 wt % to 7 wt %.
7. The method for preparing a composite forward osmosis membrane according to claim 1, wherein In step S2, the first predetermined time is 5 minutes to 10 minutes, the second predetermined time is 5 minutes to 10 minutes, and the third predetermined time is 1 minute to 2 minutes.
8. The method for preparing a composite forward osmosis membrane according to claim 1, wherein In step S1, the stirring time is 1 min to 10 min, and the standing time is 2 h to 5 h; In step S2, the standing still specifically includes the steps of: standing still in the air for 1 min to 5 min; the heat treatment specifically includes the steps of: heat treatment at 40°C to 60°C for 5 min to 10 min.
9. A composite forward osmosis membrane, characterized in that: The composite forward osmosis membrane is prepared by the preparation method according to any one of claims 1 to 8.
10. An application of reverse salt diffusion lithium extraction using the composite forward osmosis membrane as claimed in claim 9, characterized in that: The reverse salt diffusion lithium extraction method is applied to separate magnesium and lithium in a magnesium-lithium mixed solution, extract lithium in salt lake brine, or extract lithium in a waste lithium battery leachate.